2022
DOI: 10.34188/bjaerv5n2-032
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia do herbicida indaziflam no controle das plantas daninhas perenes Digitaria nuda, Rottboellia exaltata e Panicum maximum no desenvolvimento inicial da cana-de-açúcar / Efficacy of the herbicide indaziflam in the control of perennial weeds Digitaria nuda, Rottboellia exaltata and Panicum maximum in the initial development of sugarcane

Abstract: Entre as plantas daninhas de maior importância para a cana-de-açúcar estão as espécies da família Poaceae, cujo método de controle mais utilizado é o químico com uso de herbicidas aplicados em pré-emergência, entre os quais se destaca o indaziflam. Portanto, o objetivo deste trabalho foi avaliar a eficácia de três doses do herbicida indaziflam (75, 150 e 225 g de p.c.ha-1) na presença e ausência de palha de cana-de-açúcar no controle das três espécies de plantas daninhas perenes Digitaria nuda, Rottboellia exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The herbicides trifluralin, pendimethalin, and indaziflam did not differ from each other in reducing the dry mass of the species, showing a lower control compared to the associations of herbicides, with control values ranging from 70.0 to 85.8%. The results obtained for the treatment of indaziflam applied alone agree with those found by Rodrigues et al (2022), who found a higher reduction in dry matter of R. exaltata when applied at a dose of 75 g ha −1 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The herbicides trifluralin, pendimethalin, and indaziflam did not differ from each other in reducing the dry mass of the species, showing a lower control compared to the associations of herbicides, with control values ranging from 70.0 to 85.8%. The results obtained for the treatment of indaziflam applied alone agree with those found by Rodrigues et al (2022), who found a higher reduction in dry matter of R. exaltata when applied at a dose of 75 g ha −1 .…”
Section: Resultssupporting
confidence: 89%
“…Similar to the other pre-emergent herbicides, an increase in control was observed over the course of the evaluations, with a 70% control of R. exaltata plants at 35 and 42 DAA. Similarly, Rodrigues et al (2022) found that the herbicide indaziflam at doses of 75 and 150 g ha −1 promoted control higher than 95% of R. exaltata at 35 and 49 DAA. Table 4 shows the results of the germination of R. exaltata seed for the different treatments as a function of the evaluation times.…”
Section: Resultsmentioning
confidence: 79%